Prevalence and Associated Factors of Psychological Distress Among Diabetic Patients at Thyolo District Hospital in Malawi: A Hospital-Based Cross-Sectional Study [Letter] - Jayte M (Diabetes, Metabolic Syndrome and Obesity, 2024)
Mohamed Jayte Internal Medicine Department at Kampala International University, Kampala, UgandaCorrespondence: Mohamed Jayte, Internal Medicine Department at Kampala International University, P.O. Box 7062, Kampala, Uganda, Tel +256 55272543, Email jayte.mohamed@studwc.kiu.ac.ug